Application of the Jerold E Kemp Learning Model in PAI Subjects in Class XI SMAN 1 Sindangbarang Cianjur Regency - Syahrul Mu'min, Wandi; Safwandy Nugraha, Mulyawan; Dedih, Ujang (Zona Education Indonesia, 2024)
The aim of this research is to explain the application of PAI learning using the JEROLD E.KEMP model and students' responses to the application of the J.E KEMP model at SMA Negeri 1 Sindangbarang. This research approach uses qualitative with Grounded Theory type. Meanwhile, the informants are Islamic Religious Education teachers and students from class XI of SMA Negeri 1 Sindangbarang. Data collection techniques use observation, interviews and documentation. And data analysis techniques are carried out by data reduction, data display and data verification. Research states that the buying and selling material which is the subject matter in class their respective competencies, thus the activity will motivate students to be creative and create new things that have selling value. The results of this research show that (1) The stages (syntax) of PAI learning using the J.E KEMP model determine general objectives, make an analysis of student characteristics, prepare the selection of appropriate teaching materials/materials, determine teaching materials/materials, the teacher carries out tests starting with students, determining facilities and infrastructure, conducting evaluations. (2) The students' response to the model provided was very positive, the students were enthusiastic in carrying out the learning